Anxiety among the Vietnamese Population during the COVID-19 Pandemic: Implications for Social Work Practice. Issue 2 (17th February 2021) - Nam, Pham Tien; Dung, Nguyen Hanh; Liem, Nguyen Khac; Hung, Nguyen Tuan; Ly, Dang KimKhanh; Van Minh, Hoang
ABSTRACT: The COVID-19 pandemic is a global health crisis and threatening human lives, especially vulnerable groups. This study aimed to estimate the prevalence of self-reported anxiety and to examine associated factors among the Vietnamese population during the COVID-19 pandemic. A cross-sectional study in Vietnam was conducted in April 2020. An online survey was used to do the rapid assessment. Among 1, 249 participants, the prevalence of self-reported anxiety was 8.5%. In the multivariable regression models, significant factors for self-reported anxiety were people aged 60 years old or older, rural areas, and COVID-related music-video-watching. Implications for social work practice were also discussed.